Порівняння результатів корекції міопії слабкого ступеня методами RELEX SMILE та FEMTO-LASIK - Завгородня, Наталія Григорівна; Завгородня, Т. С.; Костровська, Катерина Олегівна; Поплавська, Ірина Олександрівна; Безденежна, Ольга Олександрівна; Кривобок, Н. С.; Zavgorodnya, N. G.; Zavgorodnya, T. S.; Kostrovska, K. O.; Poplavska, I. O.; Bezdenezhna, O. A.; Kryvobok, N. S. (My University, 2021)
Мета: порівняти ефективність, безпечність та прогнозованість результатів корекції міопії слабкого ступеня методами Femto-Lasik та ReLEx Smile. The comparison was performed by the methods of ReLEx Smile and Femto-Lasik in lowgrade myopia. According to the obtained results, ReLEx Smile promotes faster recovery of the cornea after surgery and better retains its elastic properties compared to the femto- Lasik method.
Comparison of the results of low-grade myopia surgery using RELEX SMILE and FEMTO-LASIK methods